A new species of whip spider, Sarax sinensis sp. nov., from Fujian, China (Arachnida: Amblypygi: Charinidae) - Wu, Shi-Yang; Zhu, Xiao-Yu; Liu, Yi-Jiao; de Miranda, Gustavo Silva; Román-Palacios, Cristian; Li, Zheng; He, Zhu-Qing (Zootaxa, 2022)
To date, only two whip spider species have been recorded in China. We describe a new species, Sarax sinensis sp. nov., from Fujian, China. This species is morphologically similar to S. ioanniticus (Kritscher, 1959), S. israelensis (Miranda et al., 2016), and S. seychellarum (Kraepelin, 1898), but can be distinguished by the combination of the following characters: 35 segments in leg I tarsus, eight teeth on cheliceral claw, and four dorsal and ventral spines respectively on pedipalp femur. To examine the evolutionary history of S. sinensis sp. nov., we sequenced 12S, 16S, and COI gene regions of our specimens and inferred its phylogenetic position. The inferred phylogenetic trees placed the new species within Sarax, with its closest relative being distributed across the western Asia. The type specimens are deposited in the Museum of Biology, East China Normal University (ECNU).